GEOMORPHOLOGICAL ANALYSIS OF THE MARMARIK RIVER BASIN. EXOGENIC PROCESSES (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
The conditions and causes of formation of exogenic processes that are wide spread in the basin of the Marmarik River are considered. The composition of weathering rocks, their filtration ability, considerable daily fluctuation in air temperature, high partition of mountain slopes, their gradient and shape, large altitudes of the relief and existence of vertical differentiation, nature of plant cover and erosion stability of soils, as well as a breach of nature by humans provoking the formation of dangerous exogenic processes are discussed.
Keywords: exogenic processes; ravines; landslides; debris flows; stream erosion